Extraction of Betacyanins from Hylocereus polyrhizus Peels Using Aqueous Two-Phase System - Vo, Thi Nga; Tran, Minh Tien; Hoang, Minh Hao (Journal of Technical Education Science, 2023)
Hylocereus polyrhizus, known as red dragon fruit provides a betacyanin pigment source, which is not only concentrated in the flesh but also present in the peel with high content. Betacyanins are beautiful red-violet pigments used as food additives and stable in a wide pH range from 3 to 6. However, the stability of betacyanins is affected by heat, which causes discoloration. The aim of this work was to report the extraction of betacyanins from red dragon fruit peels by an aqueous two-phase system (ATPS) to overcome the drawback. By applying the aqueous two-phase extraction (ATPE) method on Hylocereus polyrhizus peels, the highest betacyanin yield of 85.07% was obtained in the optimal conditions of ammonium sulfate (12.75%, w/w); ethanol (30.00%, w/w); dragon fruit peel (8%, w/w), and pH 5.0 at 30 oC.